Stability analysis of slag heap in “scoop-shaped” valley area based on multi-profile residual thrust method - Yanyan YU; Yi ZHAO; Yi FANG; Minfeng LU; Jiewen ZHU; Zhaohui TANG; Bo CHAI (Shuiwen dizhi gongcheng dizhi, 2025)
Due to the basic advantages of being surrounded by mountains on three sides, most of the waste slag is selected to accumulate in the “scoop-shaped” site with high surroundings and low middle. Through the analysis of the topography and slag heap morphology of the “scoop-shaped” valley area, it is considered that there is a stress concentration at the leading edge of the slag heap, and the stability coefficient of the slag heap calculated by conventional methods may be high. Thus, it is necessary to propose an improved stability calculation method for the “scoop-shaped” slag heap site. Considering the terrain characteristics of the “big belly and small closure” of the “scoop-shaped” site, an improved multi-profile residual thrust method was proposed in this study based on the residual thrust method. The physical model slag tests with different aspect ratios and different slope gradients were carried out by using coal gangue materials to verify the rationality of the calculation method. The test results show that when the aspect ratio of the valley is between 1−2 and the slope of the valley is greater than the internal friction angle of the material, the stress concentration occurs at the leading edge of the slag heap, and the stress at the leading edge of the slag heap increases with the increase of the slope of the valley. The stability coefficient of the model slag heap is calculated by the traditional residual thrust method (single-profile method) and the multi-profile method, respectively. The calculation results of the multi-profile method are smaller than those of the single-profile method, and the residual sliding force on the main profile calculated by the multi-profile method is basically consistent with the monitoring data, with the error of less than 5%. Therefore, the multi-profile residual thrust method has high reliability in calculating the stability of the slag heap slope in the “scoop-shaped” site. The method can provide a basis and method support for the risk prevention and control as well as disaster prevention and mitigation engineering design of the “scoop-shaped” slag dump.